2023
DOI: 10.1039/d3na00397c
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of nanocrystals in cancer theranostics

Devyani Yenurkar,
Malay Nayak,
Sudip Mukherjee

Abstract: Emerging cancer cases across the globe and treating them with conventional therapies with multiple limitations have been challenging for decades. Novel drug delivery systems and alternative theranostics are required for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 177 publications
0
5
0
Order By: Relevance
“…These results may introduce OPE-5 molecule as a promise candidate for the encryption and medical applications. 67,68 One of the most important parameters in optoelectronics applications is the emission oscillator strength ( f em ). 69 Theoretically, for a given PL material, f em is directly proportional to the emission cross section ( σ em ) and it is given by: 70 where e is the electron charge, ε 0 is the vacuum permittivity, m e is the mass of electron, c 0 is the speed of light, n F is the refractive index of the gain material, ν is the frequency of the corresponding emission, and g ( ν ) is the normalized line shape function with ∫ g ( ν )d ν = 1.…”
Section: Resultsmentioning
confidence: 99%
“…These results may introduce OPE-5 molecule as a promise candidate for the encryption and medical applications. 67,68 One of the most important parameters in optoelectronics applications is the emission oscillator strength ( f em ). 69 Theoretically, for a given PL material, f em is directly proportional to the emission cross section ( σ em ) and it is given by: 70 where e is the electron charge, ε 0 is the vacuum permittivity, m e is the mass of electron, c 0 is the speed of light, n F is the refractive index of the gain material, ν is the frequency of the corresponding emission, and g ( ν ) is the normalized line shape function with ∫ g ( ν )d ν = 1.…”
Section: Resultsmentioning
confidence: 99%
“…For example, cellulose nanocrystals loaded with 5-fluorouracil, and salinomycin nanocrystals showed promising results in the treatment of colorectal cancer. Another study demonstrated the efficacy of albumin-coated carfilzomib nanocrystals in breast cancer therapy [ 92 ].…”
Section: Types Of Nanomaterialsmentioning
confidence: 99%
“…Nanocrystals offer advantages in drug delivery due to their high drug-loading capacity, simplified preparation process, and improved bioavailability. 130,131 In a study, the surface of Lu nanocrystals was modified with sodium dodecyl sulfate (SDS), resulting in remarkable stability in the liquid state within 30 days (Table 5). 127 Furthermore, the SDS modification facilitated the opening of tight junctions between caco-2 cells, thereby promoting the transmembrane transport of Lu.…”
Section: Nanocrystalsmentioning
confidence: 99%